Efficacy and Tolerability of STOPAIN for a Migraine Attack - St. Cyr, Andrea; Chen, Ashley; Bradley, Kathleen C.; Yuan, Hsiangkuo; Silberstein, Stephen D.; Young, William B. (Frontiers in Neurology, 2015)
Objective: To determine whether topical menthol 6% gel will relieve a migraine attack. Materials and Methods: A single-center, open-label pilot trial of 25 patients with at least 1 year of diagnosed episodic migraine and <15 headache days per month. Patients treated one migraine attack with STOPAIN topical menthol 6% gel to skull base within 2 h of headache onset. Headache pain severity was assessed prior to and after gel application. Results: Thirty-two patients enrolled and 25 completed the study. Prior to treatment, 7 patients had mild pain, 13 moderate pain, and 5 severe pain. Two hours following gel application, 7 (28%) patients had no pain, 7 (28%) mild pain, 6 (25%) moderate pain, and 5 (20%) severe pain. The majority of patients had similar pain intensity (8; 32%) or improvement (13; 52%). At 24-h, only two non-rescued patients still had mild headache. Of the 25 completers, 2 patients took rescue medication prior to the 2-h period, and an additional 10 patients rescued between 2 and 24 h. Conclusion: Study results showed a significant improvement in headache intensity by 2 h after gel application. This pilot study shows STOPAIN gel may be effective in treating an acute migraine attack.